Effects of infant feeding practice on weight gain from birth to 3 years. Issue 8 (19th November 2008) - Griffiths, L J; Smeeth, L; Hawkins, S Sherburne; Cole, T J; Dezateux, C
Abstract : Objective: The influence of infant feeding practices on weight gain during childhood remains unresolved, with few studies adjusting appropriately for confounding factors. This study examined the effect of breastfeeding initiation, breastfeeding duration and age at introduction of solid foods on weight gain from birth to 3 years. Design: Nationally representative prospective study. Setting: England, Wales, Scotland and Northern Ireland. Participants: 10 533 3-year-old children from the UK Millennium Cohort Study. Main outcome measure: Conditional weight gain z-scores from birth to 3 years (adjusted for birthweight); multiple linear regression analyses were conducted to examine the impact of infant feeding practices on this measure after adjustment for confounding factors. Results: Breastfeeding initiation and breastfeeding duration were significantly associated with weight gain from birth to 3 years. Infants receiving no breast milk grew faster than those whose mothers initiated breastfeeding (adjusted regression coefficient (difference in z-scores) 0.06, 95% CI 0.02 to 0.09), as did those breastfed for less than 4 months (0.05, 95% CI 0.01 to 0.09) versus those breastfed 4 months or longer. Early introduction of solids was not associated with faster weight gain after adjustment for height z-score at 3 years (−0.01, 95% CI −0.04 to 0.03). Conclusions: Initiating and prolonging breastfeeding may reduce excess weight gain by preschool age. Association of the early introduction of solids with rapid weight gain during early childhood is mediated through childhood stature. Although effects sizes are small, at a population level they are of public health importance as these risk factors are potentially modifiable. Strategies to support mothers to follow internationally recommended infant feeding practices are required.